Efek Antikalkuli Ekstrak Etanol Herba Seledri (Apium graveolens L.) terhadap Tikus yang Diinduksi Hidroksiprolin - Taofik Rusdiana; Lutfi Sulaiman; Eli Halimah; Ami Tjitraresmi; Sri Adi Sumiwi; Yanni D. Mardhiani; Anas Subarnas (MPI (Media Pharmaceutica Indonesiana), 2019)
The investigation efforts of an alternative treatment of the kidney stone disease by utilizing Indonesian native plants have still continued both for treatment and prevention. This study aims to strengthen the scientific evidence of the activity of celery as an anticalculi by in vivo assessment using hydroxyprolineinduced rat method. The white male wistar rats used in this study were intraperitoneally induced by hydroxyproline in order to form kidney stones, the celery extract preparations were then given at a dose of 50, 100, and 200 mg/kg of body weight orally for 5 days and observed following parameters: concentration of filtrate urinary calcium, concentration of urinary sediment calcium, as well as kidney to body weight ratio. The results showed that the concentration of filtrate urinary calcium in the test group at a dose of 200 mg/ kg body weight was significantly higher than those of negative control group, whereas the other test groups were not significantly different with the negative control group. The similar result was also shown on the parameter of calcium concentration in the urine sediment, while the ratio of kidney to body weight showed significant differences between all test groups and the negative control group. It can be concluded that the ethanol extract of the herb celery has an anticalculi activity in rats at a dose of 200 mg/kg of body weight.